2019
DOI: 10.1177/0014402919873556
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Special Educators’ Intent to Continue Teaching Students with Emotional or Behavioral Disorders in Self-Contained Settings

Abstract: Schools experience difficulty retaining special educators to serve students with emotional or behavioral disorders (EBD) in self-contained settings, as they have higher rates of burnout and attrition than other educators. Administrators could prevent these outcomes by improving working conditions, but research provides limited insights into which conditions are most important for these special educators. Using structural equation modeling to analyze data from a national survey, we found that special educators’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(131 citation statements)
references
References 30 publications
5
126
0
Order By: Relevance
“…Some evidence suggests logistical supports may also have an impact on teachers’ plans to stay. Bettini, Cumming, et al (2019) analyzed data from a national sample of SETs serving students with EBD and found that they were more likely to intend to stay in their schools when they had greater access to instructional materials and when they reported sufficient planning time. Other studies have obtained similar findings (e.g., Albrecht et al, 2009).…”
Section: Working Conditions In Special Educationmentioning
confidence: 99%
“…Some evidence suggests logistical supports may also have an impact on teachers’ plans to stay. Bettini, Cumming, et al (2019) analyzed data from a national sample of SETs serving students with EBD and found that they were more likely to intend to stay in their schools when they had greater access to instructional materials and when they reported sufficient planning time. Other studies have obtained similar findings (e.g., Albrecht et al, 2009).…”
Section: Working Conditions In Special Educationmentioning
confidence: 99%
“…One key issue for special educators is access to curricular resources and training, which can create either positive or negative working conditions (Bettini, Cumming, et al, 2020; Billingsley et al, 2020). When special education teachers are provided with curricular resources, such as textbooks, instructional materials, and scope and sequence, studies have shown a projected reduction in stress and teachers identified they are more likely to stay in the profession.…”
Section: The Importance Of Curricular Resourcesmentioning
confidence: 99%
“…Access to curricular resources has been demonstrated to be beneficial for teacher retention (Billingsley et al, 2020) and supportive in teachers’ ability to make effective instructional decisions (Siuty et al, 2018). Even teacher planning time can be more effective when provided with instructional materials, as teachers can use time for planning instead of creating materials (Bettini, Cumming, et al, 2020). Kaufhold et al (2006) surveyed 228 elementary special education teachers in Texas.…”
mentioning
confidence: 99%
“…In contrast, special educators without adequate planning time sometimes report using instructional time for planning and paperwork, suggesting that providing more planning time could translate into more time for instruction (Bettini et al, 2015). In addition, researchers have consistently found that special educators’ ratings of planning time are associated with their emotional exhaustion (a component of burnout that is related to instructional quality) and intent to continue teaching (Bettini et al, 2020). Thus, providing and protecting planning time for special educators may support effective reading instruction as well as have collateral benefits through prevention of teacher burnout and attrition.…”
Section: Administrators’ Roles In Supporting Special Educators’ Readimentioning
confidence: 99%